2011
DOI: 10.1038/oby.2011.45
|View full text |Cite
|
Sign up to set email alerts
|

Intramyocellular Lipid and Insulin Resistance: Differential Relationships in European and African Americans

Abstract: Insulin resistance has been associated with the accumulation of fat within skeletal muscle fibers as intramyocellular lipid (IMCL). Here, we have examined in a cross-sectional study the interrelationships among IMCL, insulin sensitivity, and adiposity in European Americans (EAs) and African Americans (AAs). In 43 EA and 43 AA subjects, we measured soleus IMCL content with proton-magnetic resonance spectroscopy, insulin sensitivity with hyperinsulinemic–euglycemic clamp, and body composition with dual-energy X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 45 publications
4
40
2
Order By: Relevance
“…BAI was previously shown to diverge from %BF measurements at the extremities of the range in Caucasian adults [29]. Previous studies showed increased insulin resistance in African American compared to Caucasian women [31]. However, hip circumference in African American women can be wider than in Caucasian and Filipina women without manifestation of any characteristics of the MetS, thus hip circumference may be a less accurate indicator of body adiposity in older African American women because of differences in fat distribution [32].…”
Section: Discussionmentioning
confidence: 99%
“…BAI was previously shown to diverge from %BF measurements at the extremities of the range in Caucasian adults [29]. Previous studies showed increased insulin resistance in African American compared to Caucasian women [31]. However, hip circumference in African American women can be wider than in Caucasian and Filipina women without manifestation of any characteristics of the MetS, thus hip circumference may be a less accurate indicator of body adiposity in older African American women because of differences in fat distribution [32].…”
Section: Discussionmentioning
confidence: 99%
“…Results: Fasting glucose, 2-hour glucose, waist circumference, and blood pressure components contributed similarly for the prediction of future diabetes (CMDS scores,23,21,26,and 20, respectively). The area under the receiver operating characteristic curve was 0.7158 for the CMDS scoring system, whereas it was 0.7053 for the Framingham diabetes score.…”
Section: Main Outcome Measures: Incident Diabetesmentioning
confidence: 93%
“…Vastus lateralis biopsies were performed after an overnight fast as described (7). Adipose tissue was removed and samples were divided, frozen in liquid nitrogen, and stored at Ϫ80 C. All tissue samples were carefully treated without reducing agents and with only two freeze-thaw cycles since collection (one after tissue collection and the other after preparing homogenate).…”
Section: Methodsmentioning
confidence: 99%
“…Reactive aldehydes such as 4-hydroxynonenal (HNE) are biomarkers of lipid peroxidation and have been associated with intramyocellular lipid (IMCL) accumulation in sedentary individuals (4). It is widely postulated that lipid peroxides modify mitochondrial proteins and critical components of the insulin signaling pathway (5,6), leading to impaired stimulation of glucose uptake, mitochondrial damage, and additional oxidative stress, thereby propagating a deleterious cycle (7). However, few data have been reported to substantiate this theory.…”
mentioning
confidence: 97%